Caffeine-carbohydrate mouth-rinsing counter-acts an observed negative effect of mouth-rinsing procedure during sprint-endurance training performance in fasted athletes: A pilot study - Washif, Jad; Hébert-Losier, Kim; Chamari, Karim; Beaven, Christopher (Biology of Sport, 2022)
Carbohydrate mouth-rinsing has been reported to benefit endurance performance in athletes intermittently fasting; however, in the fasted state, the effects of combined caffeine and carbohydrate (CAF-CHO) mouth-rinsing on sprint-endurance performance are unknown. We determined the effects of CAF-CHO mouthrinsing on kinetics, kinematics, and perceptual measures during a sprint-endurance performance commonly performed by track and field athletes in Muslim athletes fasting during Ramadan. In a randomised and counterbalanced single-blind study, ten national-level male sprinters and sprint/middle-distance runners (21.0 ± 2.0 y) participated in this study. They performed three sprint-endurance sessions on a non-motorised treadmill within the second and third weeks of Ramadan. Each session consisted of 3x15-s all-out sprints, with 2-min active recovery between each sprint. In each session, athletes either did not mouth rinse (NMR), or rinsed with 25 mL of CAF-CHO (4 g carbohydrate, 5 mg caffeine), or a placebo solution (PLA) prior to warm-up (30-min pre-trial), 1-min pre-trial, and mid-way through every recovery period. CAF-CHO maximised total sprint distance relative to NMR (210.3 ± 7.8 vs. 208.7 ± 9.1 m, d = 0.20), whilst counteracted the attenuation following PLA (204.6 ± 8.7 m; d = 0.66). Relative to NMR, CAF-CHO increased perceived activation prior to each sprint (p 0.05). Athletes indicated ‘no’ (50%) or ‘unsure’ (50%) whether mouth-rinsing would improve performance. The results suggest that CAF-CHO has a potential to optimise, and counter-act the negative effect of mouth-rinsing in Ramadan-fasted Muslims having a negative attitude towards this procedure.